ANALISIS KRITIS TERHADAP KANDUNGAN AJARAN AGAMA ISLAM DALAM KEGIATAN OSIS SMA NEGERI DI KALIMANTAN SELATAN - Samdani Samdani; Muhdi Muhdi; Isny Lellya (Fakultas Pertanian, 2022)
Since the 2000s the issue of radicalism has emerged in Indonesia. According to the Directorate of Deradicalization of the BNPT (2018), there are several indicators that someone can be categorized as an adherent of radicalism, including spreading anti-Pancasila ideology. and joining an invitation to support groups for the caliphate associated with the global terror network of the Islamic State (ISIS), Puslitjak Dikbud in 2017 found evidence that it was known that 8.2% of students agreed-strongly agreed if the OSIS Chair at their school was of the same religion and 6.8 % of students feel that it is better if the Student Council Chair is of the same ethnicity or ethnicity, and this shows the seeds of exclusive understanding which if they continue to develop will lead to radicalism appearing within the student council organization. This study uses a type of field research with data collection techniques through a survey of OSIS administrators and members of State Senior High Schools in South Kalimantan. This study aims to illustrate what lines contribute to the color of radicalism in the OSIS activities of State Senior High Schools in South Kalimantan towards the religious understanding and attitudes of OSIS members of State Senior High Schools in South Kalimantan.